1997
DOI: 10.1002/(sici)1097-0215(19970328)71:1<123::aid-ijc20>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reaction between antibodies raised against the last 20 C-terminal amino acids of BRCA 1 (C-20) and human EGF and EGF-R in MCF 10a human mammary epithelial cell line

Abstract: Cross-reaction between antibodies raised against the last 20 C-terminal amino acids of BRCA 1 (C-20) and human EGF and EGF-R in MCF 10a human mammary epithelial cell lineA recent publication of Wilson et al. (1996) reported on the specificity of rabbit polyclonal antibodies raised against a peptide corresponding to amino acids 1843-1862 mapping at the carboxy terminus of human BRCA 1 (C-20), commercially available from Santa Cruz Biotechnology (Santa Cruz, CA). Surprisingly, this antiserum cross-reacted with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…BRCA1 has been claimed to be an exclusively nuclear protein in both normal and cancer cells (Scully et al 1996;Thomas et al 1996;Thakur et al 1997;Wilson et al 1999), a nuclear protein in normal cells but an aberrantly localized cytoplasmic protein in breast and ovarian tumor cells (Chen et al 1995;Lee et al 1999), and a cytoplasmic protein found in tubelike structures that invaginate the nucleus (Coene et al 1997). The variation in the subcellular localization of BRCA1 might be attribut- able to several causes, including the specificity of the antibodies used to localize the protein, antibody crossreactivity (Smith et al 1996;Bernard-Gallon et al 1997;Wilson et al 1999), and the presence of splice variant isoforms (Thakur et al 1997;Wilson et al 1997). The present study confirms that BRCA1 is expressed as both nuclear and cytoplasmic antigen in breast cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…BRCA1 has been claimed to be an exclusively nuclear protein in both normal and cancer cells (Scully et al 1996;Thomas et al 1996;Thakur et al 1997;Wilson et al 1999), a nuclear protein in normal cells but an aberrantly localized cytoplasmic protein in breast and ovarian tumor cells (Chen et al 1995;Lee et al 1999), and a cytoplasmic protein found in tubelike structures that invaginate the nucleus (Coene et al 1997). The variation in the subcellular localization of BRCA1 might be attribut- able to several causes, including the specificity of the antibodies used to localize the protein, antibody crossreactivity (Smith et al 1996;Bernard-Gallon et al 1997;Wilson et al 1999), and the presence of splice variant isoforms (Thakur et al 1997;Wilson et al 1997). The present study confirms that BRCA1 is expressed as both nuclear and cytoplasmic antigen in breast cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…BRCA1 protein is thought to be a nuclear protein; however, it is well known that the anti-BRCA1 antibody, C-20, crossreacts with EGFR and HER2 (4,5). Antibody C-20 is raised against residues 1843^1862 of the BRCA1 protein, and because this region is highly conserved between BRCA1 and some members of the tyrosine kinase receptor family, such as EGFR and HER2, the antibody is thus believed to cross-react with them (4).…”
Section: Resultsmentioning
confidence: 99%
“…To avoid confusion with C-20 antibodies (raised against a peptide corresponding to amino acids 1843-1862 mapping at the carboxy terminus of BRCA1) and cross reaction with the human epidermal growth factor receptor (EGF-R) and HER 2 (Wilson et al, 1996;Bernard-Gallon et al, 1997)…”
Section: Brca1 Is Localized In Ductal Secretions Of Normal Breast Tismentioning
confidence: 99%
“…To avoid confusion with C-20 antibodies (raised against a peptide corresponding to amino acids 1843-1862 mapping at the carboxy terminus of BRCA1) and cross reaction with the human epidermal growth factor receptor (EGF-R) and HER 2 (Wilson et al, 1996;Bernard-Gallon et al, 1997), we performed an immunochemical analysis of BRCA1 in comparison with a polyclonal antibody against EGF-R (Santa Cruz Biotechnology) on all 24 breast carcinoma samples. With this antibody against EGF-R, we found a very faint staining pattern in the cytoplasm and on the membrane of the mammary cells, but the secretions in the tubes of the normal breast tissue remained unstained (Fig.…”
mentioning
confidence: 99%